Purinergic Signaling in Gut Inflammation: The Role of Connexins and Pannexins - Diezmos, Erica F.; Bertrand, Paul P.; Liu, Lu (Frontiers in Neuroscience, 2016)
Purinergic receptors play an important role in inflammation, and can be activated by ATP released via pannexin channels and/or connexin hemichannels. The purinergic P2X7 receptor (P2X7R) is of interest since it is involved in apoptosis when activated. Most studies focus on the influence of pannexin-1 (Panx1) and connexin 43 (Cx43) on ATP release and how it affects P2X7R function during inflammation. Inflammatory bowel disease (IBD) is characterized by uncontrolled inflammation within the gastrointestinal system. At present, the pathophysiology of this disease remains largely unknown but it may involve the interplay between P2X7R, Panx1 and Cx43. There are two main types of IBD, ulcerative colitis and Crohn’s disease, that are classified by their location and frequency of inflammation. Current research suggests that alterations to normal functioning of innate and adaptive immunity may be a factor in disease progression. The involvement of purinergic receptors, connexins and pannexins in IBD is a relatively novel notion in the context of gastrointestinal inflammation, and has been explored by various research groups. Thus, the present review focuses on the current research involving connexins, pannexins and purinergic receptors within the gut and enteric nervous system, and will examine their involvement in inflammation and the pathophysiology of IBD.